A pan-cancer analysis of FAT atypical cadherin 4 (FAT4) in human tumors - Weili Mao; Jiajing Zhou; Jie Hu; Kui Zhao; Zhenling Fu; Jun Wang; Kaili Mao (Frontiers Media S.A., 2022)
ObjectiveWe performed a pan-cancer analysis to explore the potential mechanisms of FAT4 in 33 different tumors.MethodsIn this study, we selected 33 types of cancers based on the datasets of TCGA (the cancer genome atlas). We analyzed the expression of FAT4 in tumor and normal tissues. Meanwhile, we analyzed the expression levels of FAT4 in tissues from tumors of different stages. Kaplan-Meier survival analysis, Tumor Mutational Burden (TMB), Microsatellite Instability (MSI), immune infiltration analysis, Gene set enrichment analysis (GSEA), and FAT4-related gene enrichment analysis were performed.ResultsFAT4 expression in most tumor tissues was lower than in corresponding control tissues. FAT4 expression was different in different stages of bladder cancer (BLCA), kidney clear cell carcinoma (KIRC), and breast cancer (BRCA). In addition, the expression level of FAT4 in different types of tumors has an important impact on the prognosis of patients. FAT4 might influence the efficacy of immunotherapy via tumor burden and microsatellite instability. We observed a statistically positive correlation between cancer-associated fibroblasts and FAT4 expression in most tumors. GSEA of BLCA indicated that low FAT4 expression groups were mainly enriched in calcium signaling pathway and chemokine signaling pathway. GSEA analysis of KIRC suggested low FAT4 expression groups were mainly involved in olfactory transduction and oxidative phosphorylation. Kyoto Encyclopedia of Genes and Genomes (KEGG) indicated that the role of FAT4 in the pathogenesis of cancer may be related to human papillomavirus infection, Hippo signaling pathway, PI3K-Akt signaling pathway, etc. Gene Ontology (GO) enrichment analysis further showed that most of these genes were related to the pathways or cell biology, such as peptidyl-tyrosine phosphorylation, cell junction assembly, protein tyrosine kinase activity, etc.ConclusionOur study summarized and analyzed the antitumor effect of FAT4 in different tumors comprehensively, which aided in understanding the role of FAT4 in tumorigenesis from the perspective of clinical tumor samples. Pan-cancer analysis showed that FAT4 to be novel biomarkers for various cancers prognosis.